Physiological and yield performance of commercial rice varieties under cyclic water stress in Malaysia - Nurul-Idayu Zakaria,; Zulkarami Berahim,; Muhammad Asyraf Md Hatta,; Mohamad Husni Omar,; Rhushalshafira Rosle,; Mohd Razi Ismail,; Nik Norasma Che’ya,; Asyraf Azmi,; Mohammad Iqbal Hakim Mohd Azhan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The production of drought-tolerant rice varieties in Malaysia and the information regarding the response of local varieties to water stress are still lacking. Therefore, this experiment was conducted to determine the growth, physiological performance, molecular response, and yield of ten available rice varieties, namely MR 219, MR 220- CL2, MR 297, MRQ 76, Vietnam Hybrid, UKM RC2, UKM RC8, Putra 1, MR 303, and MR 307, under ten days of cyclic water stress. The experiment was arranged in a Randomized Complete Block Design (RCBD) with three replications. Plant height, tiller number, photosynthesis rate, stomatal conductance, transpiration rate, chlorophyll content, biomass partitioning, genotyping of SSR markers, days of harvest, and yield component were measured. Results showed that water limitations reduced tiller number per hill, while plant height, leaf dry matter, and panicle length were enhanced. It was found that MR 297 had the shortest plant height, while MR 220-CL2 had a short maturity period, a shorter panicle length, and an enhanced filled grain percentage. Putra 1 and UKM RC8 showed a higher photosynthesis rate, stomatal conductance, and transpiration rate under water limitation at 99 days after sowing (DAS). Under well-watered conditions, the total grain weight per pot of Putra 1 and MR 307 was enhanced compared to MR 219. Meanwhile, under water limitation, the total grain weight per pot of UKM RC2, MR 220-CL2, MR 307, MR 297, and Vietnam Hybrid was comparable to MR 219 and slightly enhanced in UKM RC8, Putra 1, and MR 303. Among the tested varieties, MR 220-CL2 can be selected based on early maturity criteria for the potential development of drought-tolerant varieties.